3D structure prediction of Human epididymis protein 4 (HE4), an ovarian cancer biomarker via in-silico study - Abdul Rashid, Nur Nadiah; Abdul Hamid, Azzmer Azzar; Mohamed Suffian, Izzat Fahimuddin (Persatuan Saintis Muslim Malaysia (PERINTIS), 2023)
Human epididymis protein 4 (HE4) is a biomarker which recently been studied extensively for the diagnosis of ovarian cancer. In this study, the sequence of HE4 or known as WFDC2 obtained from UniProt (ID: Q14508) was used in determining its three-dimensional (3D) structure using three different web servers: AlphaFold, I-TASSER, and Robetta. The 3D structure of HE4 is currently not available in Protein Data Bank (PDB) database, hence, the prediction was done via in-silico analysis. Each 3D structure predicted by the three web servers was then refined by Molecular dynamics (MD) simulation using GROMACS. PROCHECK and ERRAT were used in validating the three refined 3D models to identify the highest quality predicted 3D structure of the protein. The Ramachandran plots derived from PROCHECK showed 100% of the residues were in the allowed regions for AlphaFold and Robetta, while for I-TASSER, 5 residues (4.9%) were located at the disallowed region. Based on the ERRAT programme, the 3D model from AlphaFold generated the highest overall-quality-factor of 97.701, followed by Robetta and I-TASSER with 94.643 and 64.789, respectively. In accordance with these validations, AlphaFold has generated a highly accurate predicted 3D structure of HE4. The outcome of this work will be beneficial for future studies, including the in-silico analysis for diagnostic applications. This will provide better information and understanding of the interactions between the protein and ligands or other biomolecules.